Differential Macrophage Responses in Affective Versus Non-Affective First-Episode Psychosis Patients - Hughes, Heather K.; Mills-Ko, Emily; Yang, Houa; Lesh, Tyler A.; Carter, Cameron S.; Ashwood, Paul (Frontiers in Cellular Neuroscience, 2021)
Increased innate immune activation and inflammation are common findings in psychotic and affective (mood) disorders such as schizophrenia (SCZ), bipolar disorder (BD), and major depressive disorder (MDD), including increased numbers and activation of monocytes and macrophages. These findings often differ depending on the disorder, for example we previously found increases in circulating inflammatory cytokines associated with monocytes and macrophages in SCZ, while BD had increases in anti-inflammatory cytokines. Despite these differences, few studies have specifically compared immune dysfunction in affective versus non-affective psychotic disorders and none have compared functional monocyte responses across these disorders. To address this, we recruited 25 first episode psychosis (FEP) patients and 23 healthy controls (HC). FEP patients were further grouped based on the presence (AFF) or absence (NON) of mood disorder. We isolated peripheral blood mononuclear cells and cultured them for one week with M-CSF to obtain monocyte-derived macrophages. These cells were then stimulated for 24 hours to skew them to opposing phenotypes, in order to identify differences in inflammatory and alternative, anti-inflammatory responses. Following stimulation with LPS and LPS plus IFN, we found that macrophages from the NON group had diminished inflammatory responses compared to both HC and AFF groups. Interestingly, when skewing macrophages to an alternative phenotype using LPS plus IL-4, the AFF macrophages increased inflammatory production of cytokines. Receiver operating curve analysis showed predictive power of inflammatory cytokine concentrations after LPS stimulation in the AFF group versus NON group. Our results suggest dysfunctional monocyte responses in both affective and non-affective psychotic disorder, with varying types of immune dysfunction depending on the presence or absence of a mood component.